Effects of mixed liquor suspended solid concentrations on membrane bioreactor efficiency for treatment of food industry wastewater - Saed, Katayon; Megat Mohd Noor, Megat Johari; Jusoh, Ahmad; Abdullah, Abdul Ghani Liew; Nagaoka, Hiroshi; Aya, Hidenori (Elsevier, 2004)
This study investigated the impact of mixed liquor suspended solid (MLSS) concentrations on the performance of a membrane bioreactor for treating food industry wastewater. The membrane bioreactor was mainly made up of an activated sludge reactor and microfiltration hollow-fibre membrane. Two experimental procedures consisting of low and high MLSS concentrations were set up. The process at low MLSS concentrations provided a higher degree of treatment in terms of suspended solids (99.2%) and turbidity (99.73%) removals. The mean flux value of process at low MLSS concentrations (5.03 L/m2.h) was found higher than those at high MLSS concentrations (2.27 L/m2.h). Furthermore, the effectiveness of MLSS concentrations was greatly influenced by the position of the membrane modules. Higher turbidity and suspended solids removals and higher flux values were obtained with a horizontally positioned membrane module compared to a vertically placed membrane module.